El desarrollo económico regional en Italia - Campolongo, Alberto (1966)
Although it is true regional differences are evident in most countries, in Italy they have a major importance on account of the extension and intensity of underdevelopment existing in the Mezzogiorno. A problem region whose origin goes back to more than a century ago, and encompassing a little less than half the italian territory with twenty millions inhabitants, the Mezzogiorno has s reduced "per-capita" income, just half the national means. In 1950 Italy began a development policy in the Mezzogiorno; at the beginning it was direct towards improving and transforming the agricultural structure. To carry out its policy it was then created what now is known as Cassa del Mezzogiorno. The House progressively extended its influence once the forticating process of the substructure capital in the agricultural sector was firmly settled. The House has the following means of action: a) common action in the public administration through its investments; b) straight forward action of the House with resource of its own; c) facilities to foster new industrial inversions such as: customs exemptions, tax reduction, etc.; d) investments that in some obligatory proportion have to be made by semi-public enterprises. It can be said, in general, that up to now the results achieved are highly positive.